2014
DOI: 10.5414/cn108370
|View full text |Cite
|
Sign up to set email alerts
|

Saliva urea nitrogen dipstick – a novel bedside diagnostic tool for acute kidney injury

Abstract: SUN dipsticks allow the discrimination of AKIN 3 from earlier AKI stages. This low-technology approach may aid the screening of severe AKI in areas where laboratory resources are scarce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 0 publications
5
28
0
Order By: Relevance
“…This is also seen in the systemic bias as shown in figure 4 ; however, for the purpose of discrimination of levels indicating the presence of AKI at AKIN III, where BUN is higher, the underestimation appears not to affect diagnostic performance when using SUN. SUN in our data was consistent with the report of Calice-Silva et al [6] ; it was able to discriminate AKI at AKIN stage III vs. the less severe stages I and II, with a diagnostic performance comparable to BUN on every analyzed observation day ( fig. 5 and 6 ).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…This is also seen in the systemic bias as shown in figure 4 ; however, for the purpose of discrimination of levels indicating the presence of AKI at AKIN III, where BUN is higher, the underestimation appears not to affect diagnostic performance when using SUN. SUN in our data was consistent with the report of Calice-Silva et al [6] ; it was able to discriminate AKI at AKIN stage III vs. the less severe stages I and II, with a diagnostic performance comparable to BUN on every analyzed observation day ( fig. 5 and 6 ).…”
Section: Discussionsupporting
confidence: 82%
“…These analyses confirm our earlier reports on the agreement between SUN and BUN [5,6] and carry current knowledge on the diagnostic performance of SUN an additional step forward by analyzing the agreement and the diagnostic utility of SUN over a prolonged period of time (4 days) following first AKI diagnosis (as per the AKIN criteria [7] ). We have found that the agreement between BUN and SUN was comparable on all observation days, generally following a declining trend in BUN and creatinine ( fig.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations